Evaluación técnico-financiera de la inyección álcali-surfactante-polímero en pozos candidatos de un campo “A” ubicado en la cuenca de los llanos orientales (2019)
This work presents the description and geological generalities of the Field "A" of the Orientals Plains basin, operated by the company CEPSA Colombia S.A., including the stratigraphic column, sedimentary model, petrophysical analysis, mother rock, generating rock, migration of hydrocarbons and the location of each stratum to be treated. The recovery methods used in this field are also explained and described. Next, different cases of study are presented contemplating the production tests, pressure tests, well completions, distance to the facilities, continuity of sand bodies, recovery factor and reserves which allow to select among the existing wells the necessary conditions to obtain different scenarios of chemical injection tests of ASP. Through the use of reservoir simulation software CMG (Computer Modeling Group), several scenarios are presented where the chemical injection simulation is carried out, where different well arrangements and combinations of alkali, surfactant and polymer chemical agents are presented. Once the simulation scenarios were developed, the recovery factor obtained in each case was observed, in order to determine which of them have greater recovery factor. Additionally, a comparison of results between the case studies developed in the CMG reservoir simulator and the results of a CEOR pilot project implemented in a field of the Eastern Plains Basin operated by the company CEPSA Colombia S.A. Finally, the financial viability of the different cases of the chemical injection study of Field "A" is evaluated through cash flow projections and financial statements, which, based on the Net Present Value (NPV) indicator, determines whether there is performance or return of the investment made.